Predictors for Antipsychotic Dosage Change in the First Year of Treatment in Schizophrenia Spectrum and Bipolar Disorders - Ringen, Petter Andreas; Reponen, Elina Johanna; Vedal, Trude Seselie Jahr; Andreassen, Ola A.; Steen, Nils Eiel; Melle, Ingrid (Frontiers in Psychiatry, 2019)
Background: Use of antipsychotic medication is central in the treatment of psychotic disorders. However, there is limited knowledge about prescription practice of antipsychotics in the critical early phase of these disorders. Clinical guidelines recommend low dosages, but no discontinuation of antipsychotic medication during the first year of treatment in first episode patients. The main aim of this study was to identify clinical predictors for dosage change or discontinuation of antipsychotics during this period. Methods: A total of 426 antipsychotic-using patients with schizophrenia spectrum or bipolar disorder, including both a first treatment sample and a sample of patients with previous treated episodes (“multi-episode” sample) from the same diagnostic groups, underwent thorough clinical and sociodemographic assessment at study baseline and after 1 year. Prescribed dosage levels at baseline and follow-up and change in dosage or discontinuation of antipsychotics from baseline to follow-up were compared between groups, controlling for possible confounders. Results: We found reduced dosages over the first year in both first treatment groups across diagnoses, but not in multi-episode groups. Weight increase predicted dosage reduction in the schizophrenia group, while the level of psychotic symptoms at baseline predicted dosage reduction in the bipolar group. We found higher baseline levels of antipsychotic use in the schizophrenia group than in the bipolar group. Conclusion: We found indications of a trans-diagnostic reduction of prescribed dosages of antipsychotics over the first year in treatment, but with different predictors for this reduction in the two diagnostic groups. The findings increase the understanding of drivers of early medication change in psychotic disorder.